2020
DOI: 10.37394/232015.2020.16.22
|View full text |Cite
|
Sign up to set email alerts
|

Profitability and Constraints of Small-Scale Tomato Production in Baubau Municipality of Southeast Sulawesi

Abstract: The study aimed to examine the profitability and find out the production constraints of small-scale tomato farming. The study was undertaken in Bau-Bau Municipality in Southeast Sulawesi province. Respondents consisted of 26 farmers who were selected from the total population of 104 tomato farmers. Data were collected using questionnaires and in-depth interviews. Data analysis was performed using cost and returns analysis, R/C ratio, and descriptive statistics. The average net returns per growing season of thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 24 publications
1
6
0
Order By: Relevance
“…In Africa, one of the limiting factors impeding tomato production is biotic stress. This is induced by the living components of the environment [15] such as weeds, insect pests and diseases [2,[16][17][18]. In an attempt to address this situation, the indiscriminate use of chemicals such as pesticides which is harmful to human health [19] and the environment [18,20] has made the demand-led breeding approach environmentally safe.…”
Section: Breeding For Resistance/tolerance To Biotic Stressesmentioning
confidence: 99%
See 1 more Smart Citation
“…In Africa, one of the limiting factors impeding tomato production is biotic stress. This is induced by the living components of the environment [15] such as weeds, insect pests and diseases [2,[16][17][18]. In an attempt to address this situation, the indiscriminate use of chemicals such as pesticides which is harmful to human health [19] and the environment [18,20] has made the demand-led breeding approach environmentally safe.…”
Section: Breeding For Resistance/tolerance To Biotic Stressesmentioning
confidence: 99%
“…This is induced by the living components of the environment [15] such as weeds, insect pests and diseases [2,[16][17][18]. In an attempt to address this situation, the indiscriminate use of chemicals such as pesticides which is harmful to human health [19] and the environment [18,20] has made the demand-led breeding approach environmentally safe. Plant breeding is one of the most cost-effective and environmentally friendly methods of controlling biotic stresses in tomato production.…”
Section: Breeding For Resistance/tolerance To Biotic Stressesmentioning
confidence: 99%
“…This phenomenon occurred in March 2022, which resulted in inflation increasing by 0.66%; the main contributor to this inflation, among others, came from red chili commodities (Silaban, 2022;Andi & Nailah, 2023;Hesti et al, 2024) Chili production decreased Due to significant climate change, superior varieties are needed, which are resistant to biotic stress factors and abiotic stress factors. (Surni et al, 2023) Meanwhile, if chili production is high, followed by less demand, then there will be overproduction, which will result in drastically lower chili prices. If this happens, it will be very unprofitable for farmers.…”
Section: Introductionmentioning
confidence: 99%
“…These constituents not only carry significance for human health but also hold an integral position in promoting overall well-being [14,13], apart from its nutritional importance, the huge yield of tomatoes is a boon for struggling farmers, workers, and women in developing countries as it helps to increase income and reduce inequality [15]. Iraq, especially the Kurdistan Region, is considered one of the regions in which tomato cultivation is excellent due to its favorable climatic conditions and arable areas, and despite the factors suitable for tomato cultivation, its production does not meet the needs of consumers in terms of quantity and quality [4] because of the few experiences of farmers with the operations that take place on the fruits or the risks arising during the production and marketing of tomatoes, such as weather change [10] the spread of diseases and pests [16], the amount of fertilizers and pesticides [17], untimely rainfall, and drought [10], Moreover, in conjunction with the expenses associated with land preparation and the cost of removing weeds, number of workers on tomato production by smallholder farmers, lack of improved varieties [18] ,and bad agricultural practices [19] in addition to marketing risks such as Not following appropriate and correct marketing methods, which leads to low prices and economic losses for farms between supply and demand, price discrepancies and prolonging their appearance in the markets [20] loss in production and the possibility of competition Free markets within markets [21], seasonality, quality, and location of products [22], transportation, warehousing, corruption, financing, low output demand, and absence of firms [23], these dangers lead to lower returns for producers and weaken their competitiveness and marketing ability [24]. Some studies indicate that the risks of productivity and marketing have a negative impact on tomato growers all over the world, especially developing countries including a study [4] in Iraq, where they confirmed in their study Preeminent marketing challenges encountered by tomato cultivators encompass the issues of market oversaturation and the liberalization of borders to accommodate the influx of produce imported from neighboring nations.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies indicate that the risks of productivity and marketing have a negative impact on tomato growers all over the world, especially developing countries including a study [4] in Iraq, where they confirmed in their study Preeminent marketing challenges encountered by tomato cultivators encompass the issues of market oversaturation and the liberalization of borders to accommodate the influx of produce imported from neighboring nations. [17] in Indonesia indicated that the main production constraints are irregular rainfall, the emergence of pests and diseases, low prices, poor soil IOP Publishing doi:10.1088/1755-1315/1262/10/102013 3 fertility, low productivity, and labor shortages, Whereas [25] finds that pest and disease attack, traditional methods of farming and weather dependence were the most perceived risks in Nigeria, [26]. The findings of the research conducted in Ghana substantiate that tomato cultivators are notably susceptible to climate-related and market-induced disturbances, culminating in diminished levels of production endeavors and corresponding revenues, the major challenges in tomato production in Ethiopia are tomato weed, tomato frost and transportation related problems.…”
Section: Introductionmentioning
confidence: 99%